Perencanaan Persediaan Suku Cadang (Spare Part) Mesin Tenun Sulzer Ruti Berdasarkan Analisis Keandalan - Teguh Baroto; Tutik Solikhati (Department Industrial Engineering, University of Muhammadiyah Malang, 2002)
Availability of machine spare parts is very supporting f or maintenancea ctivity conductedin order to improve the machine performance. So far, PT. Eratex Djaja often have difficulty inananging component stock particularly critical component of Sulzer Ruti machine, so it isnecesiary to deie.-ine theo ptimums tockc onditionto minimizer esultedc ost. In this researcwh ewill utilize probabiliticasl tockm odelw ith fixed amounto f order (Q systemm odel)i n ordert omake average stock in storage as low as possible considering quite high price of the criticalcomponent. In addition to this, it is also required that level of component availability ismaximized.B asedo n the stock model,w e are ablet o approachth e componenta mountr equiredf ora givenp eriodb y assumingc onsta.natv eraged efectr ate.F rom the lesealchc anb e conlusedth atthe numbero f componentms ustb e requiredf or quidet oothb lock assimetrical:6, upper meanbrake lining blue : 10, lower brake lining blue : 12, and upper front brake lining blue =15